Kuka kuluttaa Lapin alkoholia? : turismin ja rajakaupan vaikutus alkoholin kulutuslukuihin Lapin läänissä - Koskikallio, Ilpo (1982)
Summary : Who consumes alcoholic beverages in Lapland? : the impact of tourism and border trade on the consumption figures for alcoholic beverages in the Province of Lapland.